Examining cyberbullying tendency and multidimensional perceived social support status of teacher candidates - (:unkn) unknown (Sakarya University, 2017)
The teachers have a substantial role for students through consciously the Internet usage and struggle with cyberbullying. The purpose of this study is to investigate cyberbullying tendency and multidimensional perceived social support status of the teacher candidates. The participants of this research have become 412 teacher candidates as education faculty students. In this research, co-relational screening model has been used. In addition, Mann Whitney-U and Kruskal Wallis statistical analysis have been used to determine differences within variables. The findings of the study indicate that cyberbullying tendency and multidimensional perceived social support status have been differentiated in accordance with daily the Internet usage time and sexuality. Moreover, according to the attractive findings of this study, the cyberbullying tendency ratio of females has higher than males and the social support ratio of males has higher than females. © The Turkish Online Journal of Educational Technology.
Keywords: Cyberbullying; Multidimensional perceived social support; Teacher candidate